The role of ESG disclosure in enhancing profitability and market value: Insights from Saudi Arabia’s corporate landscape - Hussain, Maha Abu; Alsayegh, Maha Faisal; Boshnak, Helmi A (The Economics and Finance Letters, 2025)
This study examines the impact of environmental, social, and governance (ESG) disclosures on the value of non-financial firms listed on the Saudi Stock Exchange (Tadawul) from 2017 to 2022. It explores how ESG practices influence firm profitability and market valuation. Using earnings per share (EPS) and Tobin’s Q as firm value indicators, the study analyses 100 firms. To address endogeneity concerns, it applies the generalized method of moments (GMM). The study also examines the moderating role of firm size in ESG disclosure and performance. The results indicate that increased ESG disclosure enhances firm value, with environmental and governance factors playing a key role. Firm size, return on assets (ROA), and debt-to-equity ratio significantly impact performance. Larger firms exhibit better ESG practices, leading to higher earnings per share. This study confirms the positive relationship between ESG disclosure and firm value, emphasizing environmental and governance aspects. Firm size is a crucial factor influencing ESG adoption and financial outcomes. The study recommends mandatory ESG disclosure frameworks, sector-specific regulations, and incentives to enhance corporate transparency and sustainability. These measures can strengthen firms' market competitiveness and align them with Saudi Arabia’s Vision 2030.